Complementary DNA cloning and expression of a newly recognized high molecular mass allergen Ph1 p 13 from timothy grass pollen (Phleum pratense) - SUCK, R; PETERSEN, A; HAGEN, S; CROMWELL, O; BECKER, W.-M; FIEBIG, H (Clinical and experimental allergy, 2000)
Grass pollen extracts contain a range of different allergenic components that can be classified as having low, middle or high molecular mass. Almost 75% of patients allergic to grass pollen display immunoglobulin (Ig) E-reactivity to allergens in the high molecular mass range of 55-60 kDa. These proteins have not yet been fully characterized on the protein and DNA level. The aim of this study was to identify and characterize an allergen of the high molecular mass fraction of Phleum pratense pollen by N-terminal protein sequencing and molecular cloning. A previously uncharacterized allergen which migrates as a double band with a molecular mass of 55-60 kDa was biochemically purified and investigated by N-terminal sequencing. Subsequently, a DNA primer was designed to amplify the corresponding cDNA using PCR. The cloned cDNA and deduced amino acid sequence were compared with sequence data bases. Immunoblots carrying the recombinant expression product were developed with monoclonal antibodies and sera derived from allergic subjects. The IgE-binding capacity of natural and recombinant allergen was determined using EAST. The nucleic acid sequence as well as the deduced amino acid sequence consisting of 394 amino acids indicated homology with pollen specific polygalacturonases. Four potential sites for glycosylation and 16 cysteine residues were found. The recombinant expression product exhibited the same molecular size as the natural allergen and was clearly IgE-reactive. The newly characterized allergen Ph1 p 13, which shows homology with polygalacturonases, is clearly different from the allergen designated as Ph1 p 4 and therefore the high molecular mass fraction is composed of at least two different allergens. A possible reason why this important allergen has not been detected until now is that Ph1 p 13 and Ph1 p 4 are hardly separable by one dimensional SDS-PAGE.